2011
DOI: 10.1177/107769901108800309
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Public Relations in Investor Relations: Individual Investors' Preferred Information Types, Qualities, and Sources

Abstract: A survey targeting individual investors addressed the types, qualities, and sources of information this specific public seeks and values. In keeping with uses and gratifications theory and situational theory of problem solving, results identify specific conditions associated with investors seeking and selecting sources of information that would be considered public relations content, validating public relations and investor relations communication as having value to a specific set of individual investors. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 16 publications
2
9
0
1
Order By: Relevance
“…Our results are also consistent with prior survey studies of investor information search such as Elliott et al (2008) and Penning (2011). The survey questions used to measure investors' use of financial reports and SEC filings in the Elliott et al (2008) study have a reported mean value of 2.5 on a scale of 1 (seldom use) to 5 (often use).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results are also consistent with prior survey studies of investor information search such as Elliott et al (2008) and Penning (2011). The survey questions used to measure investors' use of financial reports and SEC filings in the Elliott et al (2008) study have a reported mean value of 2.5 on a scale of 1 (seldom use) to 5 (often use).…”
Section: Discussionsupporting
confidence: 91%
“…The survey questions used to measure investors' use of financial reports and SEC filings in the Elliott et al (2008) study have a reported mean value of 2.5 on a scale of 1 (seldom use) to 5 (often use). Penning (2011) reports a similar result from a survey of individual investors-they reported using the annual report less than 50% of the time. However, these studies do not consider information-processing limitations (i.e., surveys contain many more items than can be processed by the investor).…”
Section: Discussionsupporting
confidence: 76%
“…To tackle this problem, J.-N. Kim and J. E. Grunig (2011) proposed a more generalized theory—situational theory of problem solving (STOPS)—to expand STP’s explanatory power to a wider set of communicative actions of publics involving a problem-solving situation. There has been some testing of STOPS as a revision of STP (e.g., J.-N. Kim & J. E. Grunig, 2011; J.-N. Kim, Ni, S-H. Kim, & J. R. Kim, 2012; Penning, 2011), but further examination is necessary.…”
mentioning
confidence: 99%
“…In these countries, public relations make up the bulk of organizational communications, through which organizations form strong relationships with key audiences, which certainly contributes greatly to the achievement of their mission and strategic goals. In the reference (Penning, 2011), examined was how stockholders (investors) value public relations communication. It was found that investors value information from PR professionals (directly from a company) more than that from news media and other sources.…”
Section: Organization -Public Relationshipsmentioning
confidence: 99%